Poor sugar crop in Mauritius - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The drought that has hit Mauritius since the end of 1998 has seriously dented the sugar crop, now down to 340,000 tonnes compared with an annual potential of 625,000 tonnes. One of the worst-ever crops in the history of the island, it means a loss...